(untitled) (Revista de História da UEG (REVHIST), 2023)
Ignatius of Antioch is widely recognized as a fundamental source for the understanding of early second century Christianity. His theology and defense of a strict hierarchy in the churches adressed by him made him a very useful author for ecclesiastical writers both from his own and posterior times. In this article, however, we seek to approach Ignatius’ letters as historical documents to trace a framework of very important social relations in the communities to which he writes, the office of supervision above all. Keywords: Ignatius of Antioch. Proconsular Asia. Early Christianity.